(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study assesses the impact of algorithmic control on the job quality of food delivery gig workers in Delhi NCR. Utilizing a mixed-methods approach, quantitative surveys and qualitative interviews with 75 workers reveal significant challenges such as reduced job satisfaction, income instability, and lack of autonomy. Workers express concerns over transparency and fairness in decision- making, as well as stress due to performance metrics. Recommendations include enhancing transparency, fairness, and autonomy in platform management. Future research should explore interventions to improve job quality and the long-term effects of algorithmic control.